2010
DOI: 10.5194/angeo-28-1589-2010
|View full text |Cite
|
Sign up to set email alerts
|

Numerical considerations in simulating the global magnetosphere

Abstract: Abstract. Magnetohydrodynamic (MHD) models of the global magnetosphere are very good research tools for investigating the topology and dynamics of the near-Earth space environment. While these models have obvious limitations in regions that are not well described by the MHD equations, they can typically be used (or are used) to investigate the majority of magnetosphere. Often, a secondary consideration is overlooked by researchers when utilizing global models -the effects of solving the MHD equations on a grid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
48
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 101 publications
7
48
0
Order By: Relevance
“…Further work should investigate the long-term model effects of the starting conditions for TIE-GCM (and physics models in general). Ridley et al (2010) showed the influence of grid choice for global MHD code and it seems that something similar is happening with global ionospheric-thermospheric models.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…Further work should investigate the long-term model effects of the starting conditions for TIE-GCM (and physics models in general). Ridley et al (2010) showed the influence of grid choice for global MHD code and it seems that something similar is happening with global ionospheric-thermospheric models.…”
Section: Resultsmentioning
confidence: 84%
“…Whilst necessary, this reduction introduces inaccuracies. Ridley et al (2010) showed that solving the magnetohydrodynamics (MHD) equations numerically rather than analytically can cause significant differences in global MHD code. The same piece of code can give very different results by simply altering the numerical settings.…”
Section: Multi-model Ensemblesmentioning
confidence: 99%
“…It should be noted that a global MHD simulation does not necessarily converge towards the same solution even if resolution is improved (Ridley et al, 2010). In fact, if resolution is improved, numerical diffusion decreases, which means that the role of MHD physics as an error source grows.…”
Section: Discussionmentioning
confidence: 99%
“…The most popular solution so far has been to implement the magnetohydrodynamic (MHD) equations in a global computer simulation. The level of numerical accuracy has been discussed mainly in terms of the order of the solution (see the review by Ridley et al, 2010), while the question remains as to whether the MHD model itself is rich enough to be used as a basic tool for interpreting the system. MHD has proven to give a good description on large scales and where plasma can be described with one temperature (e.g.…”
Section: Introductionmentioning
confidence: 99%